Family caregivers' preparedness to support the physical activity of patients at risk for hospital readmission in rural communities: an interpretive descriptive study - Mary T. Fox; Jeffrey I. Butler; Souraya Sidani; An Nguyen (BMC, 2022)
Abstract Background Physical activity in the post-discharge period is important to maximize patient recovery and prevent hospital readmission. Healthcare providers have identified family caregivers as potential facilitators of patients' engagement in physical activity. Yet, there is very little research on family caregivers' perspectives on their preparedness to support the physical activity of patients, particularly those at risk for hospital readmission in rural communities. Accordingly, this study explored the challenges related to family caregivers' preparedness to support the physical activity of a recently discharged, rural-dwelling relative at risk for hospital readmission. Methods In this interpretive descriptive study, semi-structured interviews were conducted by telephone with 16 family caregivers. Interview transcripts were analyzed using thematic analysis. Results Participants were predominantly women (n = 14; 87.5%) with an average age of 49 years (range 26-67) who were the primary caregivers of a relative who had been hospitalized for a medical illness (n = 12; 75%) and was at high risk for hospital readmission. Four themes were identified: 1) family caregivers generally felt unprepared to support their relative's physical activity, 2) some family caregivers believed that rest was more important than physical activity to their relative's recovery, 3) insufficient physical activity preparation led to family caregiver-relative conflicts, and 4) to defuse these conflicts, some family caregivers wanted healthcare providers to be responsible for promoting physical activity. Conclusions Despite assertions that family caregivers are a potential source of support for patient physical activity, our findings indicate that family caregivers are largely unprepared to assume that role and that more work needs to be done to ensure they can do so effectively. We suggest that healthcare providers be conscious of the potential for family caregiver-patient conflict surrounding physical activity, assess family caregivers' ability and willingness to support physical activity, educate them on the hazards of inactivity, and provide physical activity instructions to family caregivers and patients conjointly. Preparing family caregivers to support their relative's physical activity is particularly important given the current emphasis on early discharge in many jurisdictions, and the limited formal healthcare services available in rural communities.